Strategi Pencegahan Narkoba pada Remaja Berbasis Karang Taruna Kelurahan Naga Pita Pematang Siantar - Markus Panggabean; Bengkel Bengkel; Fajar Utama Ritonga (Lembaga Pengembangan Kinerja Dosen, 2025)
Drugs are an abbreviation of narcotics and dangerous drugs. Napra which is an abbreviation of Narcotics, Paicotropics and Addictive Substances. Are substances that can affect the body, especially the central nervous system In an effort to realize a prosperous society, the seriousness of the community and government is needed to achieve it. One of the applications is a strategy in government. Qualitative descriptive research is intended to describe and illustrate existing phenomena, both natural and human engineering, which pay more attention to the characteristics, quality, interrelationships between activities, manipulation or changes in the variables studied, but rather describe a condition as it is. The only treatment given is the research itself, which is carried out through observation, interviews, and documentation. The purpose of descriptive research is to make systematic, actual and accurate recording of the facts and characteristics of a particular population or area. This study uses a qualitative approach with a descriptive research type. While the data collection technique is carried out through observation, interviews and documentation studies and for the selection of informants the author uses the Purposive sampling technique, namely samples taken intentionally. The location of this study is in Siantat Martoba District, especially in Naga Pita Village. This study aims to describe and analyze the Strategy in preventing Drugs in Naga Pita Village. The theory used in this study is the Prevention Strategy theory according to Wuccanti 2005,61. The results of this study are that the people of Naga Pita Village have not fully followed all the existing stages, they only participate in the implementation stage, and seen from the form of participation that is only in the form of thoughts and involvement not in the form of money. And for the influencing factors, it can be seen from the age and income factors.